Labour as a buffer: do temporary workers suffer? - Alison L. Booth; Marco Francesconi; Jeff Frank (University of Essex, Institute for Social and Economic Research (ISER), 2002)
In this paper we investigate whether or not there is an equal opportunities dimension to regulating equal pay and conditions for temporary work. We develop a buffer stock model of temporary work that suggests a number of reasons why ethnic minorities and women may be more likely to be on fixed-term contracts than comparable white males. Using three different British datasets (a random representative survey of households and two data sets of specific labour market groups), we then estimate the degree to which women and/or ethnic minorities are more likely to be on temporary contracts and estimate any associated wage differentials.
Keywords: 330